PENGARUH PENGGUNAAN SIM-RS TERHADAP KINERJA KARYAWAN (STUDI DI RS TRIMEDIKA KETAPANG, GROBOGAN) - Utomo, Budi; Purnami, Cahya Tri; Winarni, Sri (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2024)
In the digital era, information systems have become essential in supporting performance in various service institutions. Hospital Management Information System (HMIS) is key in enhancing service quality through the integration of hospital management processes. HMIS not only accelerates service processes and manages medical data but also supports accurate decision-making by hospital management. Hospital management information systems greatly facilitate decision-making in evaluating employee performance in carrying out their respective tasks in the installation. To examine the influence of HMIS usage on employee performance at Trimedika Ketapang Grobogan Hospital. A confirmatory quantitative study with explanatory survey method was conducted, involving 75 employees out of a total population of 160 at the hospital. Data were analyzed using Structural Equation Model (SEM – PLS). System and Information Quality significantly influence Employee Performance through User Satisfaction and System Usage. However, Service Quality does not significantly affect employee performance through user satisfaction or system usage. User Satisfaction also influences System Usage. System and information quality significantly affect employee performance through user satisfaction and system usage. Therefore, information systems that produce high-quality information can directly enhance employee performance.